Arguing for Teachers and for Friends: Eighth-graders' Sensitivity to Argumentation Features When Judging and Revising Persuasive Essays. Issue 10 (25th November 2020) - Hsin, Lisa B.; Snow, Catherine E.
ABSTRACT: A novel instrument, the Features of Excellent Arguments task (FEXA), was developed to elicit adolescents' judgments about argumentative essays displaying to varying degrees features characteristic of strong persuasive writing: academic language, rich evidence, multiple perspectives, and rhetorical appeal. We collected students' categorical choices about the purposes to which the essays were suited (e.g., convincing a friend, impressing a language-arts teacher), discussions of those choices, and a revision of their selected "least persuasive" essay. In this first study using the FEXA, we found that the essays judged most persuasive largely overlapped with those judged most likely to earn a good grade (i.e., those with rich evidence and academic language). Students explained their preferences by mentioning formal language, use of evidence, and essay structure, while their revisions of their "least persuasive" selections focused on linguistic features and on adding or elaborating reasons. Implications for argumentative writing instruction and assessment are discussed.